2017
DOI: 10.1017/jfm.2017.805
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow in a soft valve

Abstract: Fluid-structure interactions are ubiquitous in nature and technology. However, the systems are often so complex that numerical simulations or ad hoc assumptions must be used to gain insight into the details of the complex interactions between the fluid and solid mechanics. In this paper, we present experiments and theory on viscous flow in a simple bioinspired soft valve which illustrate essential features of interactions between hydrodynamic and elastic forces at low Reynolds numbers. The setup comprises a sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Park et al . (2018) estimated that the pressure difference required to close the pit, for a pit based upon measurements from Capron et al . (2014), would be about 0.5 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al . (2018) estimated that the pressure difference required to close the pit, for a pit based upon measurements from Capron et al . (2014), would be about 0.5 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Domec et al (2006) estimated that earlywood pits in Douglas-fir required pressure differences across the pit membrane from 0.02 to 0.47 MPa, although they suggested that pits in the roots required less pressure to seal. Park et al (2018) estimated that the pressure difference required to close the pit, for a pit based upon measurements from Capron et al (2014), would be about 0.5 MPa.…”
Section: Researchmentioning
confidence: 99%
“…Another example is Ledesma-Alonso et al [14], who conducted experiments on valves consisting of two flexible plates, to study under which conditions they block backflow. Finally, Park et al [15] found a nonlinear pressure-drop-flow-rate relation across a valve comprising a sphere connected to a spring in a tapering channel.…”
Section: Introductionmentioning
confidence: 99%
“…This flow asymmetry, coupled with self-regulated contractions of muscles surrounding the lymphatic channel [5], induces distributed pumping along the lymphatic channel. Although flow-response asymmetry has been described as a consequence of a nonlinear interaction between a laminar flow and deformable asymmetric leaflets [3,[9][10][11][12][13][14][15][16], our understanding of the relationship between the flow unidirectional response and the leaflets' geometry and mechanics remains limited to empirical models [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…Here, inspired by the lymphatic system [3,5,17], and building on the field of fluid-structure interaction of flexible structures [3,[9][10][11][12][13][14][15][16], we establish how flow asymmetry (i) emerges from an interplay between geometric asymmetry and nonlinearity induced by a fluid-structure interaction, and (ii) can be used to induce flow rectification, thus passively converting an oscillatory flow into a net fluid transport. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%